The Reduction of Nickel Slags by Graphite Electrodes using AC and DC Current - Dal, Ismail; Li, Nan; Grimsey, Eric (Metallurgical Society of CIM, 1997)
The reduction rates of nickel, cobalt and copper oxides from a commercial nickel smelter slag were measured using mainly graphite electrodes in the range 0 -10 volts AC and DC, and at power inputs ranging from zero to 191 watts. The initial slag contained around 0.4% nickel, and 0.1% of both cobalt and copper (as oxides). The results showed that reduction under DC was more effective and enhanced the recovery of pay metals, with the best total reductions being achieved of 91% of nickel, 75% of copper and 54% of cobalt after 45 minutes at 7.5 volts DC and 103 watts. Reduction with either coke or coal particles under zero current was improved by nitrogen stirring, with coal being a better reductant than coke. Addition of calcia to slag under DC conditions decreased the reduction rate of nickel oxide. After consideration of the results and a thermodynamic analysis, it was proposed that reduction under AC conditions occurred with the formation of a solid iron alloy at the gas/slag or graphite/slag interface followed a by secondary reduction of the bulk slag by iron. Under DC conditions, electro-deposition of pay metals seemed the dominant process, especially at high power inputs.